Molecular characterization of oil seed Brassica using RAPD markers (Bangladesh Journal of Scientific and Industrial Research, 2020)
Twelve varieties of oil seed Brassica spp. were characterized at molecular level using Random Amplified Polymorphic DNA (RAPD) primers to explore genetic diversity and to find out relationship among them. Twelve random primers used in the study generated 94 RAPD fragments and 53 (56.38%) of them were considered as polymorphic indicating high level of polymorphism within the materials. The size of amplified fragments ranged between 300-3000 bp. The values of pair-wise genetic distance ranged from 0.1613 to 0.5543. To find out phylogenetic relationships among the varieties, dendrogram based on Nei’s genetic distance was constructed using Unweighted Pair Group Method of Arithmetic Means (UPGMA) separating the 12 Brassica spp into two major clusters C1 and C2. This result will be useful for designing future breeding programmes for improvement of Brassica varieties.Bangladesh J. Sci. Ind. Res.55(1), 1-8, 2020